A Simplified, Fully Defined Differentiation Scheme for Producing Blood-Brain Barrier Endothelial Cells from Human iPSCs - Neal, Emma H. (Stem Cell Reports, 2019)
Human induced pluripotent stem cell (iPSC)-derived developmental lineages are key tools for in vitro mechanistic interrogations, drug discovery, and disease modeling. iPSCs have previously been differentiated to endothelial cells with blood-brain barrier (BBB) properties, as defined by high transendothelial electrical resistance (TEER), low passive permeability, and active transporter functions. Typical protocols use undefined components, which impart unacceptable variability on the differentiation process. We demonstrate that replacement of serum with fully defined components, from common medium supplements to a simple mixture of insulin, transferrin, and selenium, yields BBB endothelium with TEER in the range of 2,000–8,000 Ω × cm(2) across multiple iPSC lines, with appropriate marker expression and active transporters. The use of a fully defined medium vastly improves the consistency of differentiation, and co-culture of BBB endothelium with iPSC-derived astrocytes produces a robust in vitro neurovascular model. This defined differentiation scheme should broadly enable the use of human BBB endothelium for diverse applications.